Group-based diet and physical activity weight-loss interventions: a systematic review and meta-analysis of randomised controlled trials - Borek, A; Abraham, C; Greaves, C; Tarrant, M (Wiley, 2018)
Background Many weight-loss interventions are delivered in groups but evidence on their effectiveness, and characteristics associated with effectiveness, is limited. We synthesised evidence on (1) design and delivery of group-based weight-loss interventions; (2) effectiveness; and (3) associations between intervention characteristics, change techniques, and effectiveness. Methods Five online databases were searched to May 2017 for randomised controlled trials (RCTs) of group-based diet and/or physical activity interventions for overweight/obese adults (BMI ≥ 25). Intervention characteristics were synthesised narratively. Mean differences (MD) in weight loss were calculated using a random-effects meta-analysis, and sub-group analyses were conducted to identify moderators of effectiveness. Results Forty-seven RCTs reporting 60 evaluations of group-based interventions were included. MD in weight loss between intervention and control groups was −3.49 [95% CI −4.15, −2.84], −3.44 [−4.23, −2.85], and −2.56 kg [−3.79, −1.33] at follow-ups closest to 6, 12, and 24 months, respectively. Explicitly targeting weight loss, men-only groups providing feedback and dietary goals were significantly associated with greater effectiveness (p < .05). Conclusions Diet and physical activity interventions delivered in groups are effective in promoting clinically meaningful weight loss at 12 months. Intervention design and effectiveness vary considerably between studies, and evidence on what optimises the effectiveness of group-based weight-loss interventions remains limited.